A caterpillar moon - Simmons, Julia; Bookbinder, Alan (Bristol : BBC Education & Training, 1996)
Documentary of an African pygmies. Described on how they hunt a caterpillar for their food. Also stories about caterpillars in caterpillar season.
Copy available in DVD format
Antropologist, Barry Hewlett ; film editor, Andrew Hassenruck and Sue Goodsall
Keywords: Pygmies -- Africa; Caterpillars -- Africa